(untitled) (Fiep Bulletin - online, 2020)
The Physical Education Professional responsible for prescribing and monitoring personalized activities in order to serve each client in a specific way, using a methodology in their training program, capable of providing the best results is the Personal Trainner. This research was conducted before and after through a physical evaluation followed by individualized intervention over a period of 3 months, with a weekly frequency of 3 days, and reevaluation analyzing and comparing data obtained in the measurements of perimeters, BMI, skinfolds and physical tests as the sit and reach test (Wells Bank), abdominal muscle strength test, abdominal and pectoral muscular endurance test, and the VO2 max test. Individual records were also made in the evaluation and reassessment for possible comparisons. The results obtained assure the truth reported above, because the client obtained improvement in all evaluated items, despite being an athletic subject. Theoretical and practical foundations for excellence in practical application by Personal Trainers, generating subsidies to rationalize and verify which conduct is most effective with your student.